Raja Analysis of the potential and effectiveness of central market retribution revenue on the Regional Original Income (PAD) of Mimika Regency - Pakage, Charlex Luis; Umar, Hasan Basri; Ngutra, Risky Novan (Global Academy of Business Studies, 2025)
Purpose: This study aims to evaluate the potential and effectiveness of central market retribution revenue and its contribution to the Regional Original Income (PAD) of Mimika Regency. It seeks to determine whether market retribution is managed optimally and whether it provides meaningful income to the local government. Methodology: The research adopts a quantitative approach with descriptive and case study methods. Data were collected through documentation, questionnaires, and interviews conducted between 2019 and 2023. Analytical techniques included the calculation of effectiveness ratios, contribution analysis, and retribution potential assessment using standard regional financial formulas. Data validity was ensured through triangulation methods. Results: The findings indicate that the effectiveness of central market retribution collection in Mimika was consistently high, with an average rate above 90%, thereby categorized as effective. However, the contribution to overall PAD remained low, averaging only 2.03% during 2019–2023. The study also found that retribution potential was not fully realized due to incomplete trader registration, low payment compliance, and reliance on manual collection systems, which hinder transparency and efficiency. Conclusions: The study concludes that although central market retribution in Mimika Regency is effectively collected, its contribution to PAD is still minimal. This gap is primarily attributed to administrative inefficiencies and structural challenges. To maximize retribution revenue and strengthen local fiscal capacity, the government must improve trader data management, implement stronger monitoring systems, and adopt digital retribution mechanisms. Limitations: The research is limited to Pasar Sentral Timika and relies mainly on secondary financial data, which may not fully reflect informal transactions or administrative constraints. Contribution: This study contributes to regional fiscal policy literature by demonstrating the gap between potential and realized revenue, offering policy insights for enhancing local revenue through digitization, compliance enforcement, and governance reforms.